Spatial Ability: Measuring Its Contribution to Symmetry Understanding - Thayban, Thayban; Munandar, Haris; Kurniawati, Erga; Alio, La; Shuid, Ahmad Naqib bin (Universitas Negeri Malang, 2022)
The spatial ability affects the understanding of the material that is a three-dimensional representation. This study aims to calculate the contribution of spatial ability to understanding symmetry. The research method used is correlational quantitative, with Sixty-two Chemistry Department students in the fifth semester taking chemical bonding courses. Tests of spatial intelligence and familiarity with molecular symmetry were used to compile information. The Pearson product-moment test was used to analyse the data. The results showed that students' spatial ability in the high category had a positive relationship with students' success in understanding molecular symmetry.